Cooperative learning methodology in software engineering teaching - Carranza Avalos, Zalatiel (2014)
Cooperative learning is not a new academical concept. It is generic term intended for a group of learning procedures -the success of this can be easily understood- in which there are organized tasks for students that, in groups, resolve problems and learn. However, cooperation can vary depending on the nature of the assignment as well as the students characteristics. Therefore, to prove if this pedagogical formula improves academic performance thanks to interactive cooperation, the software engineering learning is analyzed; this is the first step of this quantitative investigation that plans to detail criteria procedures and results, so that specialists and people interested in the subject can replicate the procedure and follow this educative investigation line